(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This study explores the advancements and applications of coordinate systems in modern geodesy, with a particular focus on GNSS (Global Navigation Satellite Systems) technologies. It highlights the impact of multi-constellation systems, such as GPS, GLONASS, and BeiDou, on improving positioning accuracy through methods like Differential GNSS (DGNSS) and Real-Time Kinematic (RTK) positioning. The research also examines the challenges in coordinate system transformations, particularly in tectonically active regions, and the role of modern technologies in addressing these issues. The study predicts that, by 2035, GNSS systems will achieve sub-centimeter accuracy, revolutionizing industries such as urban planning, autonomous navigation, and environmental monitoring.